2013
DOI: 10.1136/bmjqs-2013-002003
|View full text |Cite
|
Sign up to set email alerts
|

A system-wide approach to explaining variation in potentially avoidable emergency admissions: national ecological study

Abstract: BackgroundSome emergency admissions can be avoided if acute exacerbations of health problems are managed by the range of health services providing emergency and urgent care.AimTo identify system-wide factors explaining variation in age sex adjusted admission rates for conditions rich in avoidable admissions.DesignNational ecological study.Setting152 emergency and urgent care systems in England.MethodsHospital Episode Statistics data on emergency admissions were used to calculate an age sex adjusted admission r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 20 publications
2
89
3
Order By: Relevance
“…It may be that factors associated with non-urgent presentations are outside the control of hospitals themselves. A study investigating variations in potentially avoidable ED presentations found that socioeconomic factors, particularly employment status, accounted for over 70% of the variation, with a further 15% explained by hospital factors and access to GPs 25. In contrast, this study only demonstrated a weak association with surrogate markers of socioeconomic status, as well as time and day of presentation, suggesting that access to GPs may play only a minor role in these low acuity ED presentations.…”
Section: Discussioncontrasting
confidence: 65%
“…It may be that factors associated with non-urgent presentations are outside the control of hospitals themselves. A study investigating variations in potentially avoidable ED presentations found that socioeconomic factors, particularly employment status, accounted for over 70% of the variation, with a further 15% explained by hospital factors and access to GPs 25. In contrast, this study only demonstrated a weak association with surrogate markers of socioeconomic status, as well as time and day of presentation, suggesting that access to GPs may play only a minor role in these low acuity ED presentations.…”
Section: Discussioncontrasting
confidence: 65%
“…This suggests that the deprivation of a community increases the rate of potentially avoidable admissions with unspecified chest pain. This corresponds to findings in a wider study of potentially avoidable admissions which found that deprivation accounted for 72% of the variation in their admission rates 5. The effect is not as powerful in our study suggesting that other factors impact on chest pain admission rates.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings reflect those of previous studies that have shown that deprivation and provision of beds are both associated with admission rates 5 6. Other studies have evaluated the role of technologies and services in reducing chest pain admissions and have produced mixed results.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…[2][3][4][5][6] Some of the variation in care may be related to patientlevel differences in clinical presentation as well as to hospital-level factors, such as local availability of primary care physicians, hospital occupancy, or access to certain health care services. [7][8][9] The wide variation in clinical management raises concerns about whether every patient is receiving the optimal care and whether the lack of a standardized approach is contributing to unnecessary health care costs. [10][11][12] Additional testing and treatment have not necessarily been found to correlate with more effective care, improved patient outcomes, or higher patient satisfaction.…”
mentioning
confidence: 99%